Cognitive Functions in Ataxia with Oculomotor Apraxia Type 2 - Klivényi, Péter; Nemeth, Dezso; Sefcsik, Tamás; Janacsek, Karolina; Hoffmann, Ildiko; Háden, Gábor P.; Londe, Zsuzsa; Vécsei, László (Frontiers in Neurology, 2012)
Background: Ataxia with oculomotor apraxia type 2 (AOA2) is characterized by cerebellar atrophy, peripheral neuropathy, oculomotor apraxia, and elevated serum alpha-fetoprotein levels. The disease is caused by a recessive mutation in the senataxin gene. Since it is a very rare cerebellar disorder, no detailed examination of cognitive functions in AOA2 has been published to date. The aim of the present study was to investigate the neuropsychological profile of a 54-year-old patient with AOA2. Methods: A broad range of neuropsychological examination protocol was administered including the following domains: short-term, working- and episodic- memories, executive functions, implicit sequence learning, and the temporal parameters of speech. Results: The performance on the Listening Span, Letter Fluency, Serial Reaction Time Task and pause ratio in speech was 2 or more standard deviations (SD) lower compared to controls, and 1 SD lower on Backward Digit Span, Semantic Fluency, articulation rate and speech tempo. Conclusions: These findings indicate that the pathogenesis of the cerebrocerebellar circuit in AOA2 is responsible for the weaker coordination of complex cognitive functions such as working memory, executive functions, speech and sequence learning.